PENGARUH KEMUDAHAN PENGGUNAAN KEPUASAN NASABAH TERHADAP LOYALITAS NASABAH BANK SWASTA - Risnah Pujawaty; Tirton Nefianto (Global Journal of Management, Accounting, and Financial Studies, e-ISSN: 3109-1539, 2026)
This study aims to determine the effect of ease of use and customer satisfaction on customer loyalty to the myBCA application in the Greater Jakarta area. The independent variables consist of ease of use and customer satisfaction, while the dependent variable consists of customer loyalty. The research population consists of all BCA customers who actively use the myBCA application in the Jabodetabek area. The sample size is 120 people, selected using non-probability sampling based on purposive sampling. Data collection was conducted through the distribution of questionnaires using a 5-point Likert scale. Data analysis techniques used multiple linear regression analysis. The results of this study prove that ease of use has an influence on customer loyalty, customer satisfaction has an influence on customer loyalty, and ease of use and satisfaction together have a very strong positive impact on the loyalty of myBCA app users in the Greater Jakarta area.